(untitled) (Singaporean Journal of Business Economics and Management, 2019)
Food is a critical commodity for human survival, and the availability of the food impacted by preserving the surplus food. The humankind has used several ways of protecting perishable foods, and cooling is one of the most convenient and widely used methods to store and transport the food. While industrial, commercial and domestic refrigerators play a significant role in the preservation, the impact on energy and environmental factors are also critical factors to be taken into consideration. This article tries to reveal the antiquity and necessity of the cooling industry worldwide in the context of green innovation and try to explore the future need for such studies.